Respuesta :
Step-by-step explanation:
The distance between the points A(-1,7) and B(-3,-5)
[tex]AB = \sqrt{ {(x2 - x1)}^{2} + {(y2 - y1)}^{2} } [/tex]
[tex]AB = \sqrt{ {( - 5 - 7)}^{2} + { ( - 3 + 1)}^{2} } [/tex]
[tex]AB = \sqrt{ { (- 12)}^{2} + {( - 2)}^{2} } [/tex]
[tex]AB = \sqrt{144 + 4} [/tex]
[tex]AB = \sqrt{148} [/tex]
[tex]AB = 2 \sqrt{37} [/tex]
[tex]AB = 12.1[/tex]
Distance between two points formula: [tex]\sqrt{(x2-x1)^2+(y2-y1)^2}[/tex]
[tex]= \sqrt{(-3-(-1))^2+(-5-7)^2}\\= \sqrt{(-2)^2+(-12)^2}\\= \sqrt{4 + 144} \\= \sqrt{148} \\= 12.1655...[/tex]
Round if necessary.
12.1655 ≈ 12.12
Therefore, the distance between both points is 12.1655... or 12.12
Best of Luck!